Stay - Milchan, Arnon; Lassally, Tom; Kopeloff, Eric; Forster, Forster; Benoff, David; Twentieth Century Fox (Beverly Hills, CA : 20th Century Fox Home Entertainment, 2006)
Henry, a college student, plans to kill himself in three days, unless psychologist Sam can save him. After his first encounter with Henry, Sam finds he's losing his own grip on reality, as he is thrust into a nightmarish place between life and death
Title from container
Keywords: Psychologists -- United States -- Drama; Suicide -- United States -- Prevention -- Drama; Thrillers (Motion pictures, television, etc.); Horror films